Double thin film-based sandwich-cell carrier design for multicellular tissue engineering. (5th April 2016) - Ciftci, Sait; Barthes, Julien; Lavalle, Philippe; Özçelik, Hayriye; Debry, Christian; Dupret-Bories, Agnes; Vrana, Nihal Engin
Abstract: Many organs are multicellular and each cell type requires a different microenvironment. Thus, there is a need for modular structures where the microenvironment of each cell type can be tuned separately. Herein, we describe enzymatically crosslinked gelatin based double layered film structures where each layer can be loaded with growth factors separately. As a model, we have developed a bi-layer system to produce a respiratory epithelium. This system constitutes an in vitro "epithelial patch" that can be adhered to the lumen of any implant. Crosslinking of the patches with transglutaminase resulted in 7 days of stability at 37 °C. The film layer was first used to release growth factors and it was shown that the release significantly improved the proliferation over 5 days. A549 human lung epithelial cells were used and under the release of an epithelial growth supplement mix, there was a significant improvement on the epithelial proliferation (p < 0.01). The designed substrate was successfully attached to titanium implants and we demonstrated the stability of the epithelial patch under in vitro conditions for 7 days without deterioration. Under co-culture conditions for three days both cell types were alive. Such patches can be used to obtain fast epithelialization of large implant surfaces. Graphical abstract: Highlights: A double layered sandwich-based transferable epithelial patch for mimicking connective tissue/epithelial tissue interactions Each layer can be loaded with growth factors; the efficacy of release on cell proliferation was demonstrated. This system can be applied to implants to facilitate epithelialization which is demonstrated by adhesion to titanium implants